Push-off asymmetry and kinetic strategies in functional ankle instability during continuous vertical jump tasks - Lin, Mingjie; Wang, Zilong; Lu, Jie; Shao, Weibo; Meng, Lingyue; Zhang, Qiuxia; Wang, Xiangdong (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveTo investigate the kinetic performance, power decline trajectory, and lower limb load asymmetry characteristics during the push-off phase of a 30-repetition continuous vertical jump task in individuals with functional ankle instability (FAI), and to reveal potential motor control deviations under cyclic high-output conditions.MethodsEleven males with unilateral FAI and eleven healthy control participants were recruited to complete a task consisting of 30 continuous double-leg vertical jumps. Kistler force plates and Visual3D software were utilized to extract relevant kinetic data and corresponding asymmetry indices. A linear mixed model (LMM) was constructed based on jump order to analyze kinetic trajectories. Furthermore, the rate of power decline was quantified via individual regression slopes and compared between groups.Results(1) The FAI group exhibited significantly higher asymmetry in peak vertical ground reaction force (vGRF) (p = 0.030). (2) While no significant Group × Jump Order interaction was observed for overall jump height or impulse (p > 0.05), the FAI group presented a significantly flatter decline slope in peak vGRF compared to controls (p = 0.046), indicating a distinct output strategy rather than a general performance failure.ConclusionAlthough individuals with FAI are capable of maintaining overall power output levels comparable to healthy controls during cyclic high-output tasks, they exhibit an unbalanced load distribution and a “low amplitude–low decline” kinetic output mode. This reflects a compensatory motor control structure formed over the long term. Bilateral load asymmetry and the rhythm of output decline are more indicative of potential control deficits than overall performance metrics. Future assessment and rehabilitation should prioritize the restoration of strength, neuromuscular control, and kinetic balance on the affected side to improve dynamic stability under fatigue conditions and reduce the risk of re-injury.